1979
DOI: 10.1111/j.1752-0606.1979.tb00552.x
|View full text |Cite
|
Sign up to set email alerts
|

The Uses and Abuses of Co‐Therapy

Abstract: The literature on co‐therapy suggests increased interest in this treatment procedure. There is some agreement over advantages and disadvantages, but there is also confusion on indications and counter‐indications. This paper summarizes the current use and abuse of co‐therapy. The reported clinical experiences of several co‐therapist teams, including spouse co‐therapists, are also discussed. It appears that co‐therapy will remain controversial until outcomes are rigorously measured and compared with the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Co-therapy has also been criticised (e.g., Bowers & Gauron, 1981;Foulks, 1975;Haley, 1987). The main areas of criticism include (i) expense (Haley, 1987;Hendrix et al, 2001, p. 68), (ii) the difficulty of managing the personal differences of co-therapists (Berger, 2002;Foulks, 1975, p.109), (iii) a potential for reducing the therapist's ability to take 'decisive and immediate action' (Hendrix et al, 2001, p. 68), and (iv) potential erotic issues between co-therapists that could become problematic (Russell & Russell, 1980).…”
Section: Building On the Experience Of A Reflecting Teammentioning
confidence: 99%
“…Co-therapy has also been criticised (e.g., Bowers & Gauron, 1981;Foulks, 1975;Haley, 1987). The main areas of criticism include (i) expense (Haley, 1987;Hendrix et al, 2001, p. 68), (ii) the difficulty of managing the personal differences of co-therapists (Berger, 2002;Foulks, 1975, p.109), (iii) a potential for reducing the therapist's ability to take 'decisive and immediate action' (Hendrix et al, 2001, p. 68), and (iv) potential erotic issues between co-therapists that could become problematic (Russell & Russell, 1980).…”
Section: Building On the Experience Of A Reflecting Teammentioning
confidence: 99%
“…Livingston (2001) asserted that a "good enough" relationship between coleaders can facilitate a restructuring of participants' relational patterns and rules. Others, notably L. W. Hoffman and Hoffman (1981), Low and Low (1975), Roller and Nelson (1991), and Russell and Russell (1970) have noted that married therapists who colead or engage in cotherapy run the risk of disturbing the equilibrium of their marital relationship. Thus, the coleader dyad is cautioned to intentionally attend to these relationship issues (Bowers & Gauron, 1981;S.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Group dynamics (e.g., group stage, roles) can have an impact on the coleader relationship as well, and unresolved conflict between leaders can promote splitting within the group (Heilfron, 1969;Yalom, 1995Yalom, , 2005. Finally, monetary concerns about sharing cotherapy fees in practice settings can further complicate issues (Roller & Nelson, 1991;Russell & Russell, 1970); if these concerns are effectively addressed by the leaders, the resolution of these issues can facilitate dyadic and group development (B. Levine, 1991).…”
Section: Coleadership Disadvantagesmentioning
confidence: 99%
“…Too often female-male co-therapy teams reinforce patterns of behavior that are oppressive to women (Gingras-Baker, 1976). Russell and Russell (1979) indicated that a typical scenario is a senior professional who is a male psychiatrist and a relative neophyte in family therapy, leading a female psychologist, psychiatric nurse, or social worker who is much more experienced in the area of family therapy. To avoid this problem, Rice and Rice .…”
Section: Judson L Reese-dukes Carolyn Reese-dukesmentioning
confidence: 99%
“…In addition to modeling an egalitarian relationship, femalemale co-therapists must be able to talk freely through their own relationship problems, (Reding & Ennis, 1964;Russell & Russell, 1979) and exceptional care must be taken in maintaining their relationship.…”
Section: Judson L Reese-dukes Carolyn Reese-dukesmentioning
confidence: 99%